Detection of indoxyl sulfate levels in dogs and cats suffering from naturally occurring kidney diseases. Issue 3 (September 2015) - Cheng, F.P.; Hsieh, M.J.; Chou, C.C.; Hsu, W.L.; Lee, Y.J.
Highlights Plasma concentrations of indoxyl sulfate (IS), a protein-bound uraemic toxin, are correlated with renal disease severity. Plasma IS concentrations of dogs and cats were determined by HPLC with a fluorescence detector. Both azotaemic dogs and cats had significantly higher plasma IS levels than non-azotaemic controls. The plasma IS level was significantly correlated with BUN, serum creatinine and phosphate levels. The IS concentration increased gradually as CKD severity increased, with the highest level in IRIS stage 4.